Yongqian Dynasty "the internal affairs Office of the Office of the archives" artisan reward and punishment system literature review - Jia, Ruoqi; Gao, Jiyang (Transactions on Economics, Business and Management Research, 2024)
In the Archives of the Ministry of Internal Affairs, the reward and punishment system for artisans was summarized and a relatively complete basis and measure of the reward and punishment system was extracted. In the management system of the royal family, the reward and punishment system of artisans is discussed with artisans as the research object. The treatment is determined by the quality of the skill and the amount of experience, and the reward and punishment are determined by the quality of the work and whether it is overdue. These are not only in line with the personnel management system, but also to ensure that the artisans can get reasonable remuneration for their imperial craftsmanship. Through sorting out and analyzing the records of the organization and management of artisans in Yongzheng and Qianlong years, this paper sorts out the basis of various systems and rewards and punishments in order to reveal the relationship between the organization and artisan service.